Recurrent genetic alterations in epigenetically defined pineoblastoma subtypes - Goschzik, Tobias; Yuan, Mathias; Pfaff, Elke; Müller, Manuel E. B.; Mynarek, Martin; Dörner, Evelyn; Jones, David T. W.; Pfister, Stefan; Rutkowski, Stefan; Pietsch, Torsten (Acta Neuropathologica Communications, 2025)
Previous studies have revealed four distinct epigenetic consensus pineoblastoma (PB) subtypes. The aim of this study was to confirm and further extend their respective genetic underpinnings. Cytogenetics of 83 PB were analyzed by high-resolution genome-wide molecular inversion probe analysis and methylation profiling. Seventy-nine cases were screened for mutations by next-generation DNA panel sequencing and for 25 samples mRNA expression was analyzed using NanoString. Additionally, 24 further pineal parenchymal tumors were analyzed. Clinical data of 63 patients was available. Our cohort consisted of 48 PB-miRNA1, 19 PB-miRNA2, 8 PB-MYC/FOXR2, and 8 PB-RB1 cases. PB-miRNA subtype tumors had characteristic alterations in microRNA-processing genes; DICER1 mutations (n = 19/64) and homozygous deletions of the DROSHA locus (n = 18/67) were most abundant, followed by DROSHA mutations (n = 12/64). Most frequent cytogenetic aberrations in PB-miRNA cases were chromosome 7 gains (n = 31/67) and chromosome 14 losses (n = 26/67, including 5 cases with copy-neutral LOH). The latter were significantly associated with DICER1 mutations (p < 0.001). OTX2 gain represented the most frequent alteration that occurred in 37/83 PB of all subtypes. In the PB-miRNA subtypes we identified cases with polyploid cytogenetics (n = 16/67). In contrast to previous publications, we did not find a difference in survival for the PB-miRNA subtypes, whereas PB-MYC/FOXR2 and PB-RB1 in infants showed a worse outcome. Epigenetically defined PB subtypes are characterized by distinct genetic events. Frequent gains of the oncogene OTX2 indicate a role in the pathogenesis of PB independent of its subtype.